Performance and Energy Efficiency Evaluation for HPC Applications in Heterogeneous Architectures - Klôh, Vinícius; Yokoyama, Daniel; Yokoyama, André; Silva, Gabrieli; Ferro, Mariza; Schulze, Bruno (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2018)
This work aims to analyze the aspects related to the performance, without losing focus on the energy efficiency of the applications. To this end, we evaluated a representative set of experiments with three renowned benchmarks and two real world applications used by the energy industry. These experiments used a range of environments that included a medium scale HPC system with Xeon and CUDA cores and a mobile based Jetson TX2 development board composed of ARMv8 and CUDA cores. Our results enable analysing the performance and power consumption of the selected applications, and help to energy efficiecy in HPC systems.